Methicillin-resistant Staphylococcus aureus carriage, infection and transmission in dialysis patients, healthcare workers and their family members - Lu, Po-Liang; Tsai, Jer-Chia; Chiu, Yi-Wen; Chang, Feng-Yee; Chen, Ya-Wei; Hsiao, Chin-Fu; Siu, L. K. (Nephrology, dialysis, transplantation, 2008)
Background. Carriage and subsequent infection with methicillin resistant S. aureus (MRSA) and its transmission between hospital and community settings have not been studied in dialysis patients and their contacts. Methods. Surveillance for nasal MRSA carriage and infection among dialysis patients, healthcare workers (HCWs) and their family members in a dialysis centre was prospectively undertaken during three time periods within 1 year. Molecular typing was used to determine epidemiological relationship. Results. Among 1687 samples collected, MRSA colonization rates were 2.41% (2/83) for peritoneal dialysis patients and 2.36% (12/509) for haemodialysis patients. Five (5/14) subjects subsequently had MRSA infection. The clinical MRSA isolates had the same molecular type as the colonized strains of the same person, indicating MRSA colonization preceded clinical infection. Significantly higher MRSA nasal carriage rates were observed among family members of HCWs than family members of dialysis patients (P = 0.0024). Only three major clones were observed. Pulmonary diseases (OR: 4.873, 95% CI: 1.668–14.235), recent admission to a hospital (OR: 2.797, 95% CI: 1.291–6.059) and recent antibiotics usage (OR: 2.319, 95% CI: 1.053–5.104) were also significantly associated with MRSA carriage. Conclusion. Transmission of MRSA among dialysis patients, HCWs and their family members in a dialysis unit could be inferred. Monitoring and eradication of MRSA from patients, HCWs and their family members should be considered to prevent continuous spread between healthcare facilities and the community.